Implementasi Nilai-Nilai Pancasila Mahasiswa Keperawatan Sebagai Upaya Mematuhi Kode Etik Tenaga Medis Berkualitas - Isnina, Fathimah; Syafiq, Ahmad Nur; Kurniawati, Eka; Anwari, Anwari (PGSD Universitas Muria Kudus, 2024)
This research aims to teach nursing students about the values of Pancasila which can be implemented in everyday life and also in the world of work in health services for the community. This is an effort to comply with the nursing code of ethics in the hope that nursing students can become quality medical personnel.This research is qualitative research using the library research method, while the data collection uses library data such as on Google Scholar. The researcher carried out data analysis through several stages, namely content and discourse analysis, drawing conclusions from the reading and explaining it logically and systematically. The results of research on the implementation of Pancasila values in Nursing Students' Efforts to Comply with the Code of Ethics to Become Quality Medical Personnel, namely a) The importance of practicing Pancasila b) Pancasila values c) Code of Ethics and ethical principles for nurses d) The relationship between the code of ethics and Pancasila values e) The purpose of Pancasila values being taught to nursing students. f) implementation of Pancasila values that can be applied by nursing students in accordance with the nursing code of ethics.